Desire and learning of the child: the knowledge as a possible phallic meaning - Almeida, Sàndra Francesca Conte de (Clinical Styles. The Journal on the vicissitudes of childhood, 1998)
The author stands that the acquisition of knowledge, sustained by the desire of knowing, becomes one of the possible phallic significations, written down on the symbolic order, depending on the subjective position of the child towards the Other desire, which is represented, imaginary or simbollically, by the teacher's image.